Philosophy, physics and mathematics of relative and absolute motion - Zade, Allan (International Journal of Physical Research, 2016)
The idea of motion includes propagation of signals in a given medium and motion of a physical bodies (including observers) relative to the same medium. Combinations of various types of motion lead to many phenomena detectable and hidden from the observer’s point of view.Usually, light offers the most mysterious way of motion regarding the observer. To reveal the truth and eliminate the mystery, we need to use another sophisticated way of imagination and experimentation to reach a clear view on the fundamental processes of motion despite all illusions, old ideas and wrong postulates.